Temperature-dependent fracture behavior of towpreg epoxy resins for cryogenic liquid hydrogen composite vessels: The influence of polysiloxane tougheners on the resin yield behavior. (September 2022) - Hübner, Fabian; Hoffmann, Michael; Sommer, Nicole; Altstädt, Volker; Scherer, Andreas; Dickhut, Tobias; Ruckdäschel, Holger
Abstract: In this study, a latent and tacky epoxy resin (EP) modified with siloxane core-shell-particles was developed and investigated. The use of EP as a towpreg matrix for winding of cryogenic composite vessels requires a certain toughness to resist microcracking. First, the mechanical properties at +90 °C, +22 °C, −50 °C and −196 °C were examined, with emphasis on the fracture toughness at cryogenic temperatures. Although the modulus of the resin increased dramatically, the KIC also increased by + 100% at −196 °C. Compression testing revealed that the associated yield point increased up to 500 MPa at −196 °C. The yield point of the modified resins was reduced by almost 10% which leads to easier yielding and enabling toughening mechanisms. Thus, the KIC value clearly is not the primary property that needs to be improved in cryogenics. Second, the radius of the plastic zone around the crack tip (Rp ) was calculated. It decreased mathematically from 1.9 μm to 0.4 μm, due to a reduced energy dissipation resulting from a smaller spatial expansion of the plastic deformation zone. Finally, an optimum value of 3% by volume of polydimethylsiloxane was identified, demonstrating an increase of the Rp to 1.8 μm at −196 °C and proving the necessity of combinatorial methods to understand temperature-dependent failure of epoxy matrices. Graphical abstract: Image 1 Highlights: Fracture toughness KIC measured at four temperatures from +90 °C to −196 °C. Yield behavior was modified to increase the fracture toughness and plastic zone Rp in cryogenics. Modulus and strength increase in cryogenic leads to higher crack propagation forces and decrease of Rp. SEM micrographs reveal a threshold value of toughening in cryogenics. Particles affect the β - and α -relaxation over a broad temperature range.